Recent advances in clinical practice: advances in cross-sectional imaging in inflammatory bowel disease. Issue 12 (4th August 2022) - Rimola, Jordi; Torres, Joana; Kumar, Shankar; Taylor, Stuart A; Kucharzik, Torsten
Abstract : Endoscopy remains the reference standard for the diagnosis and assessment of patients with inflammatory bowel disease (IBD), but it has several important limitations. Cross-sectional imaging techniques such as magnetic resonance enterography (MRE) and intestinal ultrasound (IUS) are better tolerated and safer. Moreover, they can examine the entire bowel, even in patients with stenoses and/or severe inflammation. A variety of cross-sectional imaging activity scores strongly correlate with endoscopic measures of mucosal inflammation in the colon and terminal ileum. Unlike endoscopy, cross-sectional techniques allow complete visualisation of the small-bowel and assess for extraintestinal disease, which occurs in nearly half of patients with IBD. Extramural findings may predict outcomes better than endoscopic mucosal assessment, so cross-sectional techniques might help identify more relevant therapeutic targets. Coupled with their high sensitivity, these advantages have made MRE and IUS the primary non-invasive options for diagnosing and monitoring Crohn's disease; they are appropriate first-line investigations, and have become viable alternatives to colonoscopy. This review discusses cross-sectional imaging in IBD in current clinical practice as well as research lines that will define the future role of these techniques.